Dry Matter and Nutrient Accumulation of Selected Green Manure Species at Different Ages on Alisols at Areka, Southern Ethiopia - Habte, Mulugeta (International Journal of Natural Sciences Research, 2014)
Continuous loss and net removal of soil nutrients from cultivated land causes a serious threat to the overall agricultural productivity. This decline in soil fertility is major constraint to agricultural production and food security in Ethiopian highland farming systems. Since farmers have limited capacity to invest in fertilizers, potential solution to the problem is to use green manure (GM) for their multiple advantages. Thus, the study was conducted to evaluate dry matter production and nutrient concentration from GM at different ages. The treatments were three levels of age (3, 4 and 5) months after planting (MAP), three GM species (Tithoniadiversifolia, Tephrosiavogelii and Crotalaria juncea) and laid out in factorial arrangement in RCBD design with three replications. T. diversifolia produced significantly (p<0.05) higher total above ground biomass (TAGB) at all ages. The TAGB yields of Tephrosiavogelii and Crotalaria juncea were lower by 35.85 and 68.82%, 32.96 and 27.12%, and 28.22 and 31.52% than the TAGB of Tithoniadiversifolia at three, four and five months after planting respectively. Nitrogen and K concentrations of all the GM species were relatively higher whereas P, Ca and Mg were low at all ages. In general, the study found appreciable dry matter yield and nutrient concentration from all species of different ages.